2016
DOI: 10.1073/pnas.1525098113
|View full text |Cite
|
Sign up to set email alerts
|

CD8+CD122+CD49dlowregulatory T cells maintain T-cell homeostasis by killing activated T cells via Fas/FasL-mediated cytotoxicity

Abstract: The Fas/FasL (CD95/CD178) system is required for immune regulation; however, it is unclear in which cells, when, and where Fas/FasL molecules act in the immune system. We found that CD8+CD122+ cells, which are mostly composed of memory T cells in comparison with naïve cells in the CD8+CD122− population, were previously shown to include cells with regulatory activity and could be separated into CD49dlow cells and CD49dhigh cells. We established in vitro and in vivo experimental systems to evaluate the regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 38 publications
3
48
0
1
Order By: Relevance
“… Immunosuppressive IL-3 Promoting dendritic cells secreting significantly less IL-12 p70 and more IL-10 [ 54 ] IL-4 Participating in both TAM and MDSC survival and the acquisition of an immune-suppressive phenotype [ 55 , 56 ]. IL-10 Inhibiting the ability of APCs to present antigens to T cells [ 57 ] Fas Inducing apoptosis of cytotoxic T lymphocytes through the FAS-FASL pathway [ 58 ] Fas ligand (FASL) Inducing apoptosis of cytotoxic T lymphocytes through the FAS-FASL pathway [ 58 ] CCL1 Specific recruitment of regulatory T cells in ovarian carcinoma fosters immune privilege [ 59 ] CCL7 Chemoattracting MDSCs and Tregs in tumor microenvironment [ 60 ]. SDF-1 Increasing immunological tolerance by polarizing Tregs [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“… Immunosuppressive IL-3 Promoting dendritic cells secreting significantly less IL-12 p70 and more IL-10 [ 54 ] IL-4 Participating in both TAM and MDSC survival and the acquisition of an immune-suppressive phenotype [ 55 , 56 ]. IL-10 Inhibiting the ability of APCs to present antigens to T cells [ 57 ] Fas Inducing apoptosis of cytotoxic T lymphocytes through the FAS-FASL pathway [ 58 ] Fas ligand (FASL) Inducing apoptosis of cytotoxic T lymphocytes through the FAS-FASL pathway [ 58 ] CCL1 Specific recruitment of regulatory T cells in ovarian carcinoma fosters immune privilege [ 59 ] CCL7 Chemoattracting MDSCs and Tregs in tumor microenvironment [ 60 ]. SDF-1 Increasing immunological tolerance by polarizing Tregs [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…11,12,17 For instance, CD8 þ T-cells can kill dendritic cells in an antigen-specific, perforin-dependent manner 18 and can regulate T-cell homeostasis by killing activated T-cells via a Fas-FasL-mediated mechanism. 19 Interestingly, a deficiency in Fas on haematopoietic cells in LDLr -/mice results in an enhanced inflammatory state 20 and a decrease in lesion stability, 21 suggesting Fas-FasL interaction is an important immune regulatory pathway in the context of hypercholesteremia. As Th1 cells are more susceptible to FasL-induced apoptosis than Th2 cells, 22 we hypothesized that the Th1 skewing effect we observed specifically in the lesions of CD8 þ T-cell depleted mice, was in part mediated through the lack of FasL-induced apoptosis.…”
Section: Fasl Blockade Increases Inflammation In Advanced Atherosclermentioning
confidence: 99%
“…In many of the systems tested so far this response is restricted by Qa-1 [38,39], an MHC Class Ib molecule expressed on effector T cells. Some reports suggested that these regulatory CD8 + T cells might use the Fas/FasL system on target T cells, CD8 + CD122 + CD49d low populations being the most effective suppressors [40]. The best evidence for a regulatory role of CD8 + T cells in SLE comes from antibody depletion [41] and genetic ablation of CD8 + T cells in lupus-prone mice [42,43].…”
Section: Chronic Activation Of Lymphocytes In Sle: B Cells Do Not mentioning
confidence: 99%